Ma’na-Cum-Maghza Sebagai Pendekatan Kontekstual dalam Perkembangan Wacana Hermeneutika Alquran di Indonesia - Adi Fadilah (Qur'an and Hadith Academic Society, 2019)
This paper seeks to uncover the theory of Ma'na-Cum-Maghza as the development of the Hermeneutic thought of the Quran introduced by Sahiron Syamsuddin and the methodology he used in developing the theory and how scholars debated the use of the term Hermeneutics in the study of the Quran in Indonesia. Through a descriptive analysis approach, I tried to present library data such as books and several scientific articles. This study concludes that there are differences of views between Muslim scholars in accepting the term Hermeneutics of the Quran, the theory offered by Syamsuddin does not came from the thought of Fazlur Rahman and Naṣr Ḥamīd Abū Zayd who put the text of the Quran as a product of historical culture, this theory explains that a reader must look for the initial meaning of the text (objective meaning) understood by the listener or the first recipient of the Quran, then sought for its significance in today's context.